PERBANDINGAN BERMAIN ORIGAMI DENGAN FINGER PAINTING TERHADAP PERKEMBANGAN MOTORIK HALUS ANAK PRASEKOLAH - Indraswari, Dewa Ayu (Coping: Community of Publishing in Nursing, 2015)
In 4 – 6 years old is a period where a certain function needs to be stimulated, as a result the child development is not slow. The result of observation from 30 students at Tunas Mekar Sari Kindergarten, there were 60% had tardiness in smooth motoric development, from 18 students at Bhuwana Kumara Kindergarten there were 45% had tardiness in smooth motoric development. This study had a purpose to know the comparison between playing origami and finger painting to smooth motoric development of preschool child. This study used Quality Experimental Design with Nonequivalent Control Group Design study plan. Sample that divided into two, there were 15 respondents of origami group and 15 respondents of finger painting group. The result of statistic test Mann Whitney Test with meaning level p < 0,05 got from score result p = 0,203 (p > 0,05), so Ho acceptance meant there was no differences between playing origami with finger painting to smooth motoric development of preschool child. This study showed that between origami and finger painting was effective to help in developing smooth motoric of preschool child. The result of this study expected teacher or parents can give origami or finger painting as one of games that can help to stimulate smooth motoric development of preschool child.
Keywords: Origami; Finger Painting; Smooth Motoric Development